Super refractory seizures with autoimmune encephalitis and ventilator associated pneumonia: a case report - Shiva, A. Priya; Shaji, Aswathy M.; Fardan, Mohammed; Yadav, K. Arun Chander (International Journal of Basic & Clinical Pharmacology, 2021)
Autoimmune encephalitis is an immune-mediated syndrome with sub-acute to chronic presentations, such as memory impairment, altered sensorium, behavioral abnormality, psychosis, and seizures. Treatment as such must not be procrastinated due to pending laboratory workup, as early recognition and initiation of therapy prevents long term neurological sequelae. This is a case report of an 11-year-old male who presented with neuropsychiatric symptoms, altered sensorium and high-grade fever which evolved into refractory status epilepticus and autonomic dysfunction. While his MRI had positive findings of encephalitis, he tested negative for infectious diseases and antibody panels.